Prediction of ECMO and Mortality in Neonates with Congenital Diaphragmatic Hernia Using the SNAP-II Score - Kipfmueller, Florian; Schroeder, Lukas; Melaku, Tamene; Geipel, Annegret; Berg, Christoph; Gembruch, Ulrich; Heydweiller, Andreas; Bendixen, Charlotte; Reutter, Heiko; Müller, Andreas (Klinische Pädiatrie, 2019)
Background The mortality of neonates with congenital diaphragmatic hernia (CDH) ranges between 20 and 40% even in specialized high-volume centers. The Score for Neonatal Acute Physiology-II (SNAP-II Score) could facilitate the decision about supportive therapies in CDH newborns.Methods The SNAP-II score consists of the variables arterial blood pressure, pH, PaO2:FiO2, body temperature, diuresis, and seizure activity and was calculated at an age of 12 h.Results 101 CDH newborns treated in our institution between 2009 and 2017 were included in the study. A SNAP-II score ≥ 28 was calculated as cutoff for predicting mortality (AUC 0.876; 95% CI: 0.795–0.957). The mortality rate was 52.9% with a SNAP-II score ≥ 28, and 5.9% with a SNAP-II score<28. Sensitivity and specificity for predicting mortality was 81.8 and 79.7%, the negative predicting value (NPV) was 94.0%, the positive predicting value (PPV) 52.9%. The optimal cutoff for predicting ECMO was ≥ 22 (AUC 0.895; 95% CI: 0.836–0.954). Sensitivity and specificity for predicting ECMO therapy was 90.7, and 63.8%, the NPV was 90.2%, and the PPV was 65% respectively. The SNAP-II score was independently associated with mortality [OR 1.126 (95% CI: 1.050–1.207)] and the need for ECMO therapy [OR 1.243 (95% CI: 1.106–1.397)].Conclusion The SNAP-II score is strongly associated with mortality and the need for ECMO therapy in CDH newborns and should be implemented in the risk stratification of these infants.
Keywords: congenital diaphragmatic hernia; SNAP-II score; risk stratification; extracorporeal membrane oxygenation; mortality